Valuation of Internet and technology stocks implications for investment analysis - Kettell, Brian. (Butterworth-Heinemann, 2002)
New ways of looking, researching and valuing these companies need to be addressed. Valuation of Internet and Technology Stocks offers practical information to enable institutional investors to value internet.coms and high tech companies more accurately. The author highlights the deficiencies in existing stock market techniques and shows how they need to be modified or, in most cases, replaced with techniques more suited for the revolution in economies which had taken place since 1991. The economic rules in the financial market place have changed to the extent that strategies successfully applied in the post war era have now been relegated to the deleted items box. 'Valuation on Internet and Technology Stocks' reviews existing stock market techniques highlighting their deficiencies and show how the New Economics necessitates new forms of investment analysis. * Investigates why there has been a high correlation between high loss companies and a rocketing stock price * Questions whether there is still a place for discounted cash flows when there is no cash flow to discount * Considers what new methods are available to value super growth companies and whether these methods are any better than existing techniques.